Analisis Kebutuhan Pengembangan Multimedia Interaktif Berbasis Lectora Inspire untuk Meningkatkan Kemahiran Bahasa Mandarin - Efendi, Chandra; Gulo, Fakhili; Raharjo, Makmum (Fenghuang: Jurnal Pendidikan Bahasa Mandarin, 2023)
The Chinese language has developed rapidly in recent years, especially after the launch of the Hanyu Shuiping Kaoshi (HSK) Chinese language proficiency test. The HSK Standardization Exam intended for foreign students consists of basic levels namely HSK 1 and HSK 2, intermediate levels namely HSK 3 and HSK 4, and high levels namely HSK 5 and HSk 6. HSK 3 which is classified as an intermediate level is the starting point for learning difficulties for foreign students in where the use of pronunciation aids began to be phased out. This study focuses on analyzing the needs of developing interactive multimedia using the Lectora Inspire application to increase the proficiency of students who have been studying for the HSK 3 exam. The ability and fluency of teachers in the use of multimedia equipment and multimedia-based learning processes is a strong foundation in future product development. The results showed that the use of interactive multimedia can help students understand HSK 3 learning and increase student motivation in learning. Students stated that the existence of interactive multimedia made the learning process more interesting and easier. This underlies the development of interactive multimedia-based HSK learning materials.